Electrothermal properties of porous ceramic fiber media containing carbon materials - Park, Sung; Kwon, Young Pil; Kwon, Hyuck Chon; Lee, Ju-Hyeon; Lee, Hae-Weon; Lee, Jae Chun (AMER SCIENTIFIC PUBLISHERS, 2007)
Electrically regenerable porous ceramic fiber media containing nanoporous carbon from 2.5% to 19.2% have been prepared for adsorption/rege ne ration system. An experimental apparatus was built for in situ measurement of the sample weight during adsorption and electrothermal desorption of gaseous adsorbates. Adsorption and electrothermal desorption behavior of gaseous adsorbates on carbon contained porous ceramic fiber media was explained by physical and electrothermal properties of these materials measured in this work. In situ thermal desorption and adsorption experiments show that a considerable amount of water vapor is adsorbed on the carbon contained media exposed to ambient air.
Keywords: DESORPTION